Communicate to inspire a guide for leaders - Murray, Kevin 1928- (London Kogan Page, 2014)
" Communicate to Inspire answers some of the key practical questions for becoming a better leader, such as: "How do you learn to be yourself, better?" and "What should you examine and how should you articulate your own purpose and values?" Kevin Murray presents a model that charts the leadership process and draws stories from his experience coaching leaders. This book offers principles of leadership communication that address: how to become more audience-centric; how to emphasize values; how to focus on the people leaders need to inspire; what methods and tools to use to try to see the world through their eyes and address their needs; and mastering the art of public speaking. Communicate to Inspire uses charts and information gathered from dozens of successful training programs to determine how to turn a department, division or company into a better listening, faster responding, more innovative entity, just by holding more and better structured conversations"--Provided by publisher.
"Inspiring leaders make us want to achieve more. They persuade us to their cause, win our active support, help us to work better together and make us feel proud to be part of the teams they create. So if we want to be better leaders ourselves, how do we communicate in a way that inspires? What do we need to think about when framing our own leadership communication? Communicate to Inspire is an essential manual for any aspiring leader, answering these key practical questions. Kevin Murray presents a model that charts the leadership process and draws stories from the years of experience he has had coaching top leaders from a wide range of organizations. He examines and analyzes some of the key successes (and failures) in leadership and provides a unique and successful model for developing your own leadership skills"--Provided by publisher.
Machine generated contents note: -- Chapter 1: Why we need a new breed of leaders -- Chapter 2: Trust, engagement, relationships and reputations: the engines of success -- Chapter 3: The 12 principles of leadership communication -- Chapter 4: How to clarify, articulate and use your passions, purpose and personal values as your leadership platform -- Chapter 5: What makes a good mission statement? The diference between good and meaningless ones -- Chapter 6: The value of values: how to make sure your values have bite -- Chapter 7: Talk about the future to drive the present -- Chapter 8: In amodern world, you need quivering antennae -- Chapter 9: Courageous conversation: the only route to success -- Chapter 10: Why you need to know how they feel, what they think, and what they're doing before you can influence -- Chapter 11: How to five them a damn good listening to -- Chapter 12: Why you need a powerful point of view to make your stand -- Chapter 13: Stories are the superglue of messages -- Chapter 14: Why you should do a 'signals' audit -- Chapter 15: How to master the art of public speaking -- Chapter 16: The essential communication planning process -- Chapter 17: The 12 questions you need to ask to check whether you're speaking the language of leaders.
Keywords: Leadership; Communication in management; Chief executive officers